Methodology for adequating parameters of the furrow irrigation method for use by irrigation extensionists. - Millar, Agustin A.; Azevedo, Hamilton M. de; Possídio, Edson L. de (Pesquisa Agropecuaria Brasileira, 2014)
A methodology for analyzing and adequating results of furrow irrigation research is described. Field data on bulk density, water retention curve, infiltration at 50% level of available water, and water advance in furrow with different slopes and flow rates: 0.15% (2.5 - 3.1 - 4 - 5 liters/sec), 0.24% (2 - 2.5 - 3 liters/sec) and 0.37% (1 - 1.5 - 2 - 2.5 liters/sec) were collected in an oxisol of the Bebedouro irrigation Project, Petrolina, PE. Effective rooting depth of crops was defined as a function of the phenological cycle. The maximum non erosive and most efficient flow rates were defined for different slope conditions. The moat efficient combinations of flow rate-slope for this soil were 2.5 liters/sec-0.15%, 2 liters/sec-0.24% and 1.5 liters/sec-037%. Field data were analyzed to answer the question How much to apply? Nomographs were prepared to be used by irrigation extensionists, for advising water application at farmer level. These nomographs, by sequential use define effective rooting depth as a function of time after planting, net water depth as a function of available water level and effective rooting depth, efficient flow rate as a function of furrow slope, application efficiency as a function of furrow length and combination of flow rate-slope, and irrigation time as a function of gross water depth and furrow length. The methodology can be extrapolated, and has to be applied in every soil.